Choosing Discourse Outcome Measures to Assess Clinical Change - Boyle, Mary (Seminars in Speech and Language, 2020)
Surveys of speech-language pathologists who work with people with aphasia indicate that they view the large number of existing measures to be a barrier to using discourse analysis in their practice. This article provides a process that can help determine whether a particular discourse outcome measure might be useful with a particular client. The process involves answering questions about the client, the treatment, the work setting, and the psychometric properties of the discourse outcome measure in question. By following this systematic process, clinicians can eliminate outcome measures that are not likely to provide useful data and can focus on those that can help them demonstrate treatment-related change.
Keywords: aphasia; discourse; outcomes